PERAN HAKIM DALAM PENEGAKAN ETIKA DAN PROFESI HUKUM - -, Hakim (Jurnal Ilmiah Ecosystem, 2016)
Professional ethics is a guide for a judge to the task it has also been statedin the policy direction of the field of law in points (5), as contained in MPRDecree No. II / MPR / 1999 on the Guidelines of State Policy, which increasesmoral integrity and professionalism of law enforcement officers, includingpolice state police of the Republic of Indonesia to foster public confidence byincreasing the effective welfare.Prosfesi ethics contained in the judge's ethics are the rules, standards, orlaws that should be adopted and hold fast by the judges, in appreciation of theirprofessions as law enforcement and justice. It will also be used to put on a goodor bad acts of judges in performing their duties even be a moral criterion in lawenforcement.While the issues discussed in this paper is how the function and role of thelegal profession ethics for judges in law enforcement? The method used in thisresearch is normative juridical approach to legislation and case. Kesimpulanyain this paper is The function and role of the legal profession ethics for judges interms of law enforcement as a guideline every judge in performing duties asjudge in giving a decision should be really concerned about ethics and fairness